ENERGY USAGE MONITORING SYSTEM FOR ENVIRONMENTAL MOBILE STATION - Sendari, S.; Rahmawati, Y.; Ramadhan, F.M.; Alqodri, F.; Tibyani, T.; Matsumoto, T.; Fujiyama, A.; Rachman, I. (Journal of Advanced Manufacturing Technology (JAMT), 2022)
This paper designed an energy usage monitoring system for the environmental mobile station (EMS). The system worked through several sensor modules that were attached to the EMS to monitor the environmental condition, i.e., carbon monoxide (CO) level, carbon dioxide (CO2) level, methane (CH4) level, temperature, humidity, wind direction, and wind velocity. The EMS used solar power energy; hence all sensor modules drained the solar power energy. Since the EMS sustainability depended on the energy from solar power and the modules' consumption, it was urgent to monitor its usage to measure the battery energy availability following the environmental conditions, such as sunny or cloudy. The harvesting energy of the solar power system was estimated using the irradiation sensor, while the energy consumption should also be monitored to gauge the drain. The result showed that the energy usage monitoring system could measure the energy availability with irradiance values ranging from 500-1000 w/m and produced the harvesting value of solar power around 14 W.